Fully Eugenol‐Based Epoxy Thermosets: Synthesis, Curing, and Properties. Issue 6 (26th December 2021) - Zhang, Yuehong; Zhai, Mengjiao; Ma, Fei; Li, Yuzhan; Lyu, Bin; Liu, Tuan; Gao, Zhenhua; Wang, Liwei; Vincent, Dan; Kessler, Michael R.
Abstract: Eugenol‐based epoxy monomer (Eu‐EP) is prepared here, followed by curing with a novel eugenol‐derived diamine (Eu‐DA) curing agent for fully eugenol‐based epoxy thermosets. The cure behavior, thermal stability, mechanical properties, and thermomechanical properties of these eugenol‐based epoxy resins are investigated and compared with a partially biobased epoxy thermoset prepared from diglycidyl ether of bisphenol A (DGEBA) and Eu‐DA. Both epoxy materials exhibit storage moduli higher than 2.1 GPa at room temperature. The tensile strength of Eu‐EP/Eu‐DA (21.9 MPa) is comparable to that of the DGEBA/Eu‐DA (24.3 MPa) thermosets and the epoxy thermoset cured from DGEBA and Eu‐DA shows a higher glass transition temperature than those from Eu‐EP and Eu‐DA. The synthesis strategy of Eu‐DA and Eu‐EP shows great potential to be applied in other biobased building blocks with hydroxyl groups. Overall, eugenol is a renewable resource to develop high value‐added chemicals and sustainable polymers with comparable properties to petroleum‐based counterparts. Abstract : Biobased epoxy thermosets are reported cured from both epoxy monomer (Eu‐EP) and diamine (Eu‐DA) curing agent derived from eugenol. The curing reaction between Eu‐DA and Eu‐EP results in a biobased epoxy resin with high biobased carbon content and excellent thermomechanical properties. The developed Eu‐DA is shown to be a sustainable curing agent for epoxy resins.